FACTORS AFFECTING STUDENT'S QUALITY IN HIGHER EDUCATION - William, William; Lubis, Tya Wildana Hapsari (Jurnal Aplikasi Manajemen, 2021)
This study aims to research the influence of student's behavior, lecturer's competency, and school's facilities on the student's quality at Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Mikroskil and Sekolah Tinggi Ilmu Ekonomi (STIE) Mikroskil Mikroskil. This research is a descriptive study with a quantitative method approach. The population in this study were undergraduate students totaling 3.493 students, the sample size used in this study is 360 students obtained using the Slovin formula. The sampling technique is stratified random sampling techniques applied to each study program. The data analysis method is multiple linear regression analysis. The results showed that student's behavior, lecturer's competency, and school's facilities had a positive and significant effect on Student's quality by 43.5 %. Future researchers are suggested to carry out the process and learning management in improving student's quality.